The Use of Oxygen/Air Blender during Transoral Laser Microsurgery with Supraglottic Manual Jet Ventilation: A Safe Approach - Sara Abu-Ghanem; James Cochran (Case Reports in Anesthesiology)
Background. Surgical fires are known, preventable, and devastating complications of transoral microlaryngeal laser surgery. Several guidelines have recommended maintaining the fraction of inspired oxygen concentration (FiO2) at or below 30% for open delivery cases. We hereby present our experience utilizing an air/oxygen gas mixing device (blender) attached to a supraglottic manual jet ventilator during transoral laser microlaryngeal surgery in three cases to control oxygen levels. Methods. Retrospective chart review of three cases and literature review. Results. Three patients underwent microlaryngeal laser surgery and balloon dilation for the management of subglottic stenosis. All three patients were successfully ventilated throughout the procedures, and no major complications occurred intraoperatively. Two of three patients demonstrated symptomatic and clinical improvement at the first follow-up. Conclusions. This report demonstrates the successful use of an oxygen/air blender to reduce FiO2 to fire-safe levels of less than 30% during laser surgery of the airway using jet ventilation.